Mastering Service Mesh Enhance, Secure, and Observe Cloud-Native Applications with Istio, Linkerd, and Consul. - Khatri, Anjali (Packt Publishing, Limited, 2020)
Service Mesh helps overcome the operational challenges of connecting, securing, controlling, and observing modern microservices deployment. This book shows you exactly how to use a Service Mesh architecture to manage and operationalize your microservices-based applications.